OPTIMIZATION OF n-HEPTANE ISOMERISATION USING NI DOPED ON ZSM5 CATALYST VIA RESPONSE SURFACE METHODOLOGY - Suleiman, Zainab U.; Chika, Muhammad; Muhammad, Aminu Bayawa; Yaquba, Muhammad Sahabi (FUDMA Journal of Sciences, 2025)
Ni-modified ZSM-5 catalysts with varying nickel contents were successfully synthesized via the impregnation method and evaluated for their catalytic activity in n-heptane isomerization. Characterization using XRD, SEM, BET, and FTIR confirmed that the structural integrity and crystallinity of the ZSM-5 framework were retained, while nickel incorporation effectively modified the acidity. BET results showed a slight decrease in surface area and pore volume with increasing nickel content. Catalytic performance was assessed in a reflux setup across a temperature range of 50–200 °C, reaction times of 20–180 minutes, and catalyst loadings from 0% to 15% Ni-ZSM-5. GC-MS analysis was used to determine product composition. Response surface methodology based on a Box-Behnken design was employed to optimize the process. The highest yield of isomerized n-heptane (84.52%) was achieved at 112 °C, 10% catalyst loading, and 180 minutes. Yields above 70% were generally obtained at higher catalyst loadings (10–14%), extended reaction times, and elevated temperatures. The results demonstrate the industrial potential of Ni-ZSM-5 as a cost-effective catalyst for octane number enhancement in gasoline production. Nickel offers a cheaper alternative to noble metals, and the moderate reaction conditions reduce operational energy demands. Additionally, the catalyst’s thermal stability and ease of preparation by impregnation make it attractive for scalable applications in the petroleum refining and petrochemical sectors.
Keywords: n-heptane isomerization; Ni-ZSM-5 catalyst; Zeolite modification; Catalytic activity; Response surface methodology; Octane enhancement